Principles of urban transport systems planning - Hutchinson, B. G. (Washington: Scripta Book Co., 1974)
This book concentrate on the techniques and knowledge that are available for the synthesis, analysis, and evaluation of alternative transport systems plan.
Includes bibliographical references.
oo 04/10/18
Loans
Keywords: Urban transportation policy; Traffic estimation